Implementation of the Brainstorming Method to Improve Learning Activities of Fourth Grade Students of SD Negeri 0104 Sibuhuan - Rizki Hamdan Saputra; Darmatua Pasaribu; Era Mutiah (Indo Journal of Multidisciplinary Science, 2026)
The type of research used is classroom action research (CAR). This research was conducted in class IV of SD Negeri 0104 Sibuhuan. The subjects in the research were class IV of SD Negeri 0104 Sibuhuan. Based on the results of the study, it can be concluded that: (1) The learning activities of class IV students of SD Negeri 0104 Sibuhuan in the pre-cycle are still low. This can be seen from the results of observations that have been carried out, the average value of student learning activities is 62.63, student learning activities with the category "Not Good" are 1 student or 5%, student learning activities with the category "Less Good" are 12 students or 63%, student learning activities with the category "Good" are 6 students or 32% and student learning activities with the category "Very Good" are 0 students or 0%. (2) The learning activities of class IV students of SD Negeri 0104 Sibuhuan in cycle I began to increase. This can be seen from the results of observations that have been carried out in cycle I, the average value of learning activities obtained by students is 72.37, student learning activities with the category "Not Good" there are 0 students or 0%, student learning activities with the category "Less Good" there are 9 students or 47%, student learning activities with the category "Good" there are 8 students or 42% and student learning activities with the category "Very Good" there are 2 students or 11%. In cycle II increased quite significantly, the average value of learning activities obtained by students is 80.78, student learning activities with the category "Not Good" there are 0 students or 0%, student learning activities with the category "Less Good" there are 9 students or 47%, student learning activities with the category "Good" there are 8 students or 42% and student learning activities with the category "Very Good" there are 2 students or 11%.